Cooperation and coopetition, determinants of openness in product innovation and human resource management. Comparative study between Spain-Portugal - Mota Veiga, Pedro; Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier (Elsevier, 2024)
The relationship between innovation and economic development has been extensively analyzed, highlighting how the national environment influences business innovation dynamics. In this context, the concept of the Triple Helix is introduced, identifying universities, firms, and governments as the main drivers of innovation development. The main objective of this paper is to deepen the understanding of the impact that cooperation and coopetition between these actors have on innovation dynamics. To achieve this, we compare two EU countries, focusing on product innovation following the Schumpeterian idea that economic development is driven by the introduction of new products. Data from 31,105 Spanish and 8224 Portuguese firms from the Community Innovation Survey (CIS) 2018 were analyzed. The results confirm that these collaborative dynamics have a positive impact on product innovation. Furthermore, human resource management is shown to be a fundamental aspect in driving innovation processes within an organization. The national context has positioned itself as a determining factor in innovation dynamics. In particular, in this study, Portuguese companies demonstrate a greater positive impact of innovation in human resources on product innovation compared to Spanish companies. The strength of this research lies in the comparative framework established between the two countries, allowing for the detection of the influence of governments, universities, and other agents in the collaborative processes that drive innovation dynamics in companies. The model proposed in this research could be extended to compare other countries, helping to explain the relationship between innovation levels and the influence of the country effect on their economic development.
Keywords: Desarrollo económico y social; Innovation; Knowledge; Cooperation; Coopetition; Human Resource Management; Spain and Portugal; Economic development